Pendekatan Hybrid Respond to Criteria Weighting dan Utalities Theory Additives untuk Pemilihan Supplier Bahan Baku dalam Industri Makanan - M Qurrota A’yun; Adhie Thyo Priandika (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Choosing the right raw material supplier is a crucial factor in maintaining quality and production continuity in the food industry. This study proposes a hybrid approach that combines the Respond to Criteria Weighting (RECA) method to objectively determine the weight of the criteria and the Utilities Theory Additives (UTA) method to evaluate alternatives based on partial utility functions. This approach is designed to accommodate the complexity of decision-maker preferences as well as the multi-criteria assessment dynamics that often occur in the supplier selection process. Case studies were conducted on several supplier alternatives by considering various criteria. The results of the ranking of alternative suppliers based on the combination of the RECA and UTA methods can be seen that the MB alternative obtained the highest score of 0.8578 as the first rank, followed in order by TM obtained a score of 0.8576 as the second rank, and AJ obtained a score of 0.8573 as the third rank. The results of the analysis show that the combination of the two methods is able to produce accurate, consistent, and relevant ratings to the strategic needs of the company. This approach makes a significant contribution to improving objectivity, transparency, and efficiency in decision-making, particularly in the food industry sector which relies heavily on supply chain reliability.